ANALYSIS OF THE PHYSICAL CHARACTERISTICS OF BIODIESEL PRODUCTS MADE FROM USED COOKING OIL - Fikria, Gina; Rustana, Cecep (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
Biodiesel is a very potential material used as a substitute for diesel fuel derived from petroleum. In manufacture of biodiesel was used waste cooking oil with FFA levels obtained which is 3.1%, so that the transesterification process is directly carried out. This study aims to find out the physical characteristics of biodiesel produced from waste cooking oil with a molar ratio of waste cooking oil to methanol 5:1 and 4:1. Method that used in this research is experiment and analytic of physical characteristics of biodiesel products made from used cooking oil. The results of the physical characteristic test of biodiesel with a ratio of 5:1 and 4:1 showed that the biodiesel density of waste cooking oil had met SNI 04-7182-2012. Viscosity test results showed that biodiesel from waste cooking oil has not met SNI 04-7182-2012. The results of flash point tests showed that biodiesel from waste cooking oil has not met SNI 04-7182-2012. Freezing point test results showed that biodiesel from waste cooking oil had met SNI 04-7182-2012. The results of the heat value test showed that biodiesel from waste cooking oil has not met SNI 04-7182-2012. And the yield shows that biodiesel from waste cooking oil has not produced a significant biodiesel yield.